Autonomous Aboriginal communities in Australia - Wimmer, Adolf (Acta neophilologica, 2009)
Discourses of Australian Aboriginal culture have all too often relied on the "noble savage" trope, in Australia as in Europe. There were practical outcomesof such views, most notably the creation of over a hundred self-governed indigenous communities in the 1980s, most of them in the Northern territories. The architect of the plan was Nuggett Coombs, a top Canberra administrator and advisor to Whitlam and Hawke. His idea was to allow Aborigines a "pre-contact" lifestyle and to shield them from all evil "white" influences. Neither worked. On the contrary, it has now emerged that the leftist, liberal consensus on how to "empower" Aboriginal culture has resulted in the exact opposite, in degradation, alcoholism, and sexual violence. This is not only due to passivity in indigenous communities but also to a decade-long denial of their dysfunctionality by the white courts, academics, and lawmakers.
Keywords: aborigini; Australia; Avstralija; degradacija; domorodske skupnosti; politics; politika